Firm Investment and Balance-Sheet Problems in Japan - Sekine, Toshitaka (IMF Working Papers; Working Paper, 1999)
This paper investigates whether balance-sheet conditions of firms and their main banks matter for firm investment behavior using dynamic corporate panel data in Japan for the period 1985-95. It finds that smaller non-bond issuing firms were facing liquidity constraints; these firms' balance-sheet conditions (the debt asset ratios) affected their investment from the midst of the bubble era by influencing main banks' lending to them; and the deterioration of their main banks' balance-sheet conditions constrained these firms' investment from about 1993. These findings highlight the potential macroeconomic impact and importance of the credit channel of monetary policy, and support the case of a credit crunch facing small Japanese firms during this period.